2023
DOI: 10.21203/rs.3.rs-2391838/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Respiratory support with nasal high flow without supplemental oxygen in patients undergoing endoscopic retrograde cholangiopancreatography under moderate sedation: a prospective, randomized, single-center clinical trial

Abstract: BACKGROUND: Nasal high flow (NHF) may reduce hypoxia and hypercapnia during an endoscopic retrograde cholangiopancreatography (ERCP) procedure under sedation. The authors tested a hypothesis that NHF with room air during ERCP may prevent intraoperative hypercapnia and hypoxemia. METHODS: In the prospective, open-label, single-center, clinical trial, 75 patients undergoing ERCP performed with moderate sedation were randomized to receive NHF with room air (40 to 60 L/min, n = 37) or low-flow O2 via a nasal cannu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…[18] Zhang YX et al [19] also indicated that efficacy of NHF not only to reduce the incidence of hypoxemia but also reduce the requirements for airway intervention during sedated digestive endoscopy procedures, especially in patients at low risk for hypoxemia. Furthermore, we have recently suggested that the application of NHF did not result in a significant reduction in the occurrence of marked hypercapnia during an ERCP procedure with www.md-journal.com [14] Therefore, this randomized clinical trial might obtain new insight to evaluate the efficacy of NHF on respiratory management. Schumann et al reported that the availability to use NHF during sedation in an endoscopy suite reduced the requirement for general anesthesia to perform complex endoscopic procedures.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…[18] Zhang YX et al [19] also indicated that efficacy of NHF not only to reduce the incidence of hypoxemia but also reduce the requirements for airway intervention during sedated digestive endoscopy procedures, especially in patients at low risk for hypoxemia. Furthermore, we have recently suggested that the application of NHF did not result in a significant reduction in the occurrence of marked hypercapnia during an ERCP procedure with www.md-journal.com [14] Therefore, this randomized clinical trial might obtain new insight to evaluate the efficacy of NHF on respiratory management. Schumann et al reported that the availability to use NHF during sedation in an endoscopy suite reduced the requirement for general anesthesia to perform complex endoscopic procedures.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, we have recently suggested that the application of NHF did not result in a significant reduction in the occurrence of marked hypercapnia during an ERCP procedure with sedation. [14] Therefore, this randomized clinical trial might obtain new insight to evaluate the efficacy of NHF on respiratory management. Schumann et al reported that the availability to use NHF during sedation in an endoscopy suite reduced the requirement for general anesthesia to perform complex endoscopic procedures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations